Synthesis and Characterization of Cobalt(II) and Nickel(II) Complexes of Substituted Isoxazoles - Vasudev Nayak, P.; Manohara, Y.N.; Mohan, S. (Asian Journal of Chemistry, 2010)
Complexes of Co(II) and Ni(II) have been synthesized using substituted isoxazole. The complexes were characterized on the basis of elemental analysis, molar conductance, IR, UV and magnetic data. Co(II) and Ni(II) complexes showed μeff indicative of their distorted octahedral structure.